Mosby's Dental drug reference 2005 - Gage, Tommy W. (Mosby, 2006)
Mosby's Dental Drug Reference 2005 is an up-to-date drug resource designed to be used chair side in the dental office. The user-friendly design provides easy access to essential information on over 1,600 of the most commonly prescribed drug products, including the top 200 prescription drugs in the United States. An easy-to-use cross index is the key to using this book for both brand and generic name identification. A second index, based on a therapeutic and pharmacologic classification, can also be used to quickly locate drug monographs.